Botulinum toxin: an endoscopic approach for treating fecal incontinence - Gourcerol, Guillaume; Bénard, Coralie; Melchior, Chloé; Touchais, Jean-Yves; Ducrotte, Phillipe; Menard, Jean-François; Bridoux, Valerie; Leroi, Anne-Marie (Endoscopy, 2016)
Background and study aims: Fecal incontinence is a common, distressing condition with limited therapeutic options. Botulinum toxin A (BTX-A) injections have been proposed as a treatment for patients with fecal incontinence. This study aimed to determine the short-term clinical outcomes of BTX-A injections in patients with fecal incontinence of varying etiology.Patients and methods: Twenty-six patients with fecal incontinence were enrolled, 17 with their native rectum and 9 with a neo-reservoir following a proctectomy for rectal cancer. BTX-A was endoscopically injected into the rectum/reservoir. Scores for severity (CCS) and quality of life (FIQL) were recorded at baseline and at the 3-month follow-up visit.Results: The CCS was significantly lower after 3 months (median 15, range 4 – 20 vs. 8, range 1 – 19; P = 0.001). The quality of life improved in three of the four FIQL domains. The improvement was maintained in 11 of 12 patients who received more than one injection because of recurrent symptoms. There was no significant predictive factor for the success of BTX-A injections.Conclusion: This preliminary study demonstrated that rectal/reservoir injections are an effective short-term treatment for fecal incontinence.